2006
DOI: 10.2139/ssrn.890944
|View full text |Cite
|
Sign up to set email alerts
|

The Goldilocks Hypothesis: Balancing Intellectual Property Rights at the Boundary of the Firm

Abstract: Recent scholarship has begun to assess the role of intellectual property rights in the theory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…In particular, Burk and Mc-Donnel (2007) document that stronger and easier to obtain downstream firm's intellectual property rights-i.e., trade secrecy and copyright instead of patents-are typically granted whenever asset specificities are particularly severe, i.e., technological businesses, such as the software industry, and the entertainment industries. 20 Furthermore, these remedies allow the downstream firm to impose on her employees and upstream partners non-disclosure agreements, work-for-hire provisions, and non-compete clauses reducing their ability to exploit proprietary information, i.e., a low γ * (Burk and McDonnel, 2007). "From the standpoint of…”
Section: Property Rights and Incomplete Contracting Costsmentioning
confidence: 99%
“…In particular, Burk and Mc-Donnel (2007) document that stronger and easier to obtain downstream firm's intellectual property rights-i.e., trade secrecy and copyright instead of patents-are typically granted whenever asset specificities are particularly severe, i.e., technological businesses, such as the software industry, and the entertainment industries. 20 Furthermore, these remedies allow the downstream firm to impose on her employees and upstream partners non-disclosure agreements, work-for-hire provisions, and non-compete clauses reducing their ability to exploit proprietary information, i.e., a low γ * (Burk and McDonnel, 2007). "From the standpoint of…”
Section: Property Rights and Incomplete Contracting Costsmentioning
confidence: 99%
“…20 First, trade secrecy and copyright arise spontaneously, upon fixation of a creative work in a tangible medium of expression, whereas patent are granted only upon the disclosure of the claimed invention (Burk and McDonnel, 2007). Second, they receive a longer protection, i.e., respectively perpetual monopoly and the author's life plus 50 to 100 years rather than the 20 years of patent protection (Burk and McDonnel, 2007).…”
Section: Robustness Checksmentioning
confidence: 99%
“…In particular, Burk and McDonnel (2007) document that stronger and easier to obtain downstream firm's intellectual property rights-i.e., trade secrecy and copyright instead of patents-are typically granted whenever asset specificities are particularly severe, i.e., technological businesses, such as the software industry, and the entertainment industries. 20 Furthermore, these remedies allow the downstream firm to impose on her employees and upstream partners non-disclosure agreements, work-for-hire provisions, and non-compete clauses reducing their ability to exploit proprietary information, i.e., a low γ * (Burk and McDonnel, 2007 …”
mentioning
confidence: 99%
“…Moreover, we have observed in previous work that while property rights work to lower transaction costs up to a point, beyond that point excessive property rights, or property rights in the wrong configuration, can work to increase transaction costs. 63 Commentators in a variety of fields have observed that fragmented rights may create a prohibitive anticommons that impede a business's freedom to operate.' Clearing a large number of licenses or obtaining a large number of permissions itself generates transaction costs.…”
Section: B the Theory Of The Irmmentioning
confidence: 99%